Innovative pathway for managing children and adolescents with mental health concerns in the emergency department: An intervention feasibility study. (3rd October 2020) - Nagarsekar, Balkrishna B; Townsend, Jackie; Ohr, Se Ok; Clapham, Matthew; Giles, Michelle
Abstract: Objective: To investigate if an innovative clinical pathway for managing child and adolescent mental health (MH) ED presentations reduces average length of stay (LOS) and improves carer satisfaction. Methods: An intervention feasibility study at an ED. Participants were 5–17 years olds presenting with MH problems and their carers. ED medical officer (MO) led Kids Assessment Liaison for Mental Health (KALM) clinical pathway was implemented as an intervention and it was compared to Care as Usual pathway which involved ED MO and MH clinicians. Data were collected via the ED clinical data system and a carer survey. Data were analysed by using SAS v9.4 (SAS, Cary, NC, USA). Survey was compared using Fisher's exact test and LOS was compared using median quantile regression. Results: Fifty (23%) patients used the KALM pathway and 169 (77%) the Care as Usual pathway. The median (min, max) LOS in hours for those on the KALM pathway was 4.13 (0.46, 11.55) compared to 5.09 (0.21, 19.12) for Care as Usual pathway ( P = 0.1407). Fewer patients breached the National Emergency Access Target (NEAT) when the KALM pathway was used (56%, n = 28 vs 64%, n = 108, P = 0.252). There were no significant differences in the carer survey between the two care pathways. Conclusion: This study provides valuable information about the benefits of the KALM pathway in managing child and adolescent MH presentations to ED. This new pathway reduces the LOS in ED and improves carer experience compared to the usual care pathway. Abstract : Kids assessment and liaison for mental health (MH) pathway at ED. Internationally, concern about meeting the need of an increasing number of children and adolescents presenting to ED with MH difficulties in an effective and timely manner is well documented. This paper describes one approach to increase capacity of ED while enhancing collaboration between ED and MH clinicians.